الفكر العقدي عند الشيخ المولود الزريبي البسكري - آية, لعويطي (جامعة الوادي university of eloued, 2023)
"امللخص تناولنا يف هذا البحث املقدم لنيل شهادة املاسرت يف العلوم اإلسالمية ختصص عقيدة، الفكر العقديعندالشيخاملولود الزرييبالبسكري)اإلهليات أمنوذجا( علىتفصيلهو كالتايل: الفصل الول: تعرضنا فيه حلياة الشيخ املولود الزرييب، من مولده ونشأته وحتصيله العلمي ورحالتهالعلمية، وفاتهوآث ره. الفصلالثاين:تناولنافيهالفكرالعقديعندالشيخاملولودالزرييبابدياألمر مدخلمفاهيمي تعريف ابلفكر العقدي وموقف مولود الزرييب من علم الكالم والتعريف بكتاب مشوس األحالم وابن عاشر ومتنه املرشد املعني، مث عرضنا ما شرحه املولود الزرييب من األبيات اخلاصة ابلعقائد مناحلكمالعقليوالصفات اإلهلية. وخلصنا من خالل هذا العمل، إىل أن للفكر العقدي أثر كبري يف حياة املفكرين والعلماء اإلسالمينييفاجلزائروخاصةيفاجلنوب الكبريالذيحيويعلىمجيعاملسائلالعقائدية. الكلمات املفتاحية:الفكر العقدي، علم الكالم، االهليات،العقائد ""Abstract In this research presented to obtain a master's degree in Islamic sciences, we dealt with the specialty of belief, the doctrinal thought of Sheikh Al-Mawlid Al-Zaribi Al-Biskari as anexample) in detail as follows: Chapter One. In it we dealt with the life of Sheikh al-Mawlud al Zumalbi, from his birth and upbringing his educational attainment and his scientific journeys, his death and its effects The second chapter we dealt with the doctrinal thought of Sheikh al Mawlid al Zumbi, at first, a conceptual introduction, a definition of doctrinal thought, the position of Mauloud al-Zuraibi on theology, and the definition of the book Shams al-Ahlam and Ibn Asher and the text of the designated guide, then we presented what al-Mawlid al-Zuraibi explained from the verses related to the beliefs of mental judgment and divine attributes . Through this work, we concluded that doctrinal thought had a great impact on the lives of Islamic thinkers and scholars in Algeria, especially in the great south, which contains all doctrinal issues. Keywords:Doctrinal thought, theology, theology, beliefs
"عقيدة
Keywords: الفكر العقدي، علم الكالم، االهليات،العقائد; Keywords:Doctrinal thought, theology, theology, beliefs